基于VB的平行分度凸轮机构参数化设计 - 陈学文; 王良文; 李安生; 唐维刚 (Jixie chuandong)
The parametric design model of parallel indexing cam mechanism is established.The parametric design is realized by second developing technology for Solidworks in VB.The outline coordinates,pressure angle and tool center coordinate of the cam can be calculated in term of selecting motion conditions.The curvature radius of the cam can be checked.This system can give out engineering drawing automatically,label dimension and technology terms,which improves the design efficiency evidently and gives a theoretical base of digital design and manufacture for the mechanism.The system’s program interface is friendly and convenient,so can be used for the engineering design and teaching.